Keunikan Tafsir Tuan Guru Hj Nik Abdul Aziz Bin Nik Mat: The Uniqueness of Tuan Guru Hj Nik Abdul Aziz Bin Nik Mat Tafsir - Abdullah, Ahmad Najib; Mohd Salleh, Nor Hazrul (Al-Basirah Journal, 2021)
Tuan Guru Dato 'Hj Nik Abdul Aziz bin Nik Mat was an affectionately known as Tok Guru, and a famous scholar who has contributed a lot of knowledge to the Muslim community in Malaysia. It was included the knowledge of tafsir Al-Qur’an. His prominence in the field of tafsir of the Qur’an and its uniqueness have not been fully studied. Thus, a study was made to highlight his prominence and survey the uniqueness of his interpretation. This is a qualitative type. Data were collected through library research methods as well as the field research by interview session and will be analyzed using inductive and deductive methods. The study also found that Tuan Guru Dato 'Hj Nik Abdul Aziz bin Nik Mat was well known as a unique tafsir figure, rich in precise, thoughtful thoughts and views in interpreting the verses of the Al-Quran.